2017
DOI: 10.15430/jcp.2017.22.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Non-homologous End Joining Inhibitor SCR-7 to Exacerbate Low-dose Doxorubicin Cytotoxicity in HeLa Cells

Abstract: Among the genotoxic drug regimens, doxorubicin (DOX) is known for its high-dose side effects in several carcinomas, including cervical cancer. This study reports on testing the combined use of a DOX genotoxic drug and SCR-7 non-homologous end joining (NHEJ) inhibitor for HeLa cells. An in vitro DNA damaging assay of DOX was performed on plasmid and genomic DNA substrate. In vitro cytotoxicity was investigated using trypan blue dye exclusion, DNA metabolizing, and propidium iodide-based flow cytometric assays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Results showed that in case of MCF-7 conditioned media, there is an increase in HeLa cell apoptotic death with respect to untreated control. Similarly, TNBC tissue non-cellular factors demonstrated more apoptotic death in HeLa cells, which is comparable to the results of doxorubicin treatment as the positive control (Kumar et al, 2017) which showed the presence of PI stained HeLa. The cell cycle analysis represented in Figure 3D and 3E depicts that the percentage of HeLa cells in G0/G1 phase significantly decreased from 66% to 41% and at the same time S phase distribution of HeLa cells increased from 11% to 25%.…”
Section: Flow Cytometry Analysis Of Hela Proliferation and Deathsupporting
confidence: 72%
“…Results showed that in case of MCF-7 conditioned media, there is an increase in HeLa cell apoptotic death with respect to untreated control. Similarly, TNBC tissue non-cellular factors demonstrated more apoptotic death in HeLa cells, which is comparable to the results of doxorubicin treatment as the positive control (Kumar et al, 2017) which showed the presence of PI stained HeLa. The cell cycle analysis represented in Figure 3D and 3E depicts that the percentage of HeLa cells in G0/G1 phase significantly decreased from 66% to 41% and at the same time S phase distribution of HeLa cells increased from 11% to 25%.…”
Section: Flow Cytometry Analysis Of Hela Proliferation and Deathsupporting
confidence: 72%
“…Breast cancer cells were incubated for 72 h at 37 °C. The rest of the procedure was adopted as per the routine protocol [ 39 , 40 ]. The absorbance was recorded using an ELISA reader (Thermo Fisher Scientific, Waltham, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we have reported that combinatorial treatment of SCR7 and radiation led to the accumulation of unrepaired DSBs, activation of apoptosis, and a ≥ 2-fold reduction in the effective IR dose in cancer cell lines and mouse tumour models [24,25,52]. Studies from other research groups have also revealed the combinatorial potential of SCR7 with radiation and chemotherapeutic agents [9,26,29]. Nucleus is stained in red using propidium iodide, while green signal represents 53BP1 foci (FITC).…”
Section: Scr116 and Scr132 Can Induce Synergistic Effects When Combin...mentioning
confidence: 99%